PENGARUH ETIKA, PENGALAMAN KERJA, SINISME TERHADAP INDEPENDENSI (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2005)
Independency is the most important thing of public accountant. Behavior of accountancy department's students (students of universities) is needed to be observed since they/are leaders of the future and also the auditors. However, this subject is intersting to be examined thoroughly because independency is closely related with auditor, aprofession which needs public trust. The writer scrutinizes many factors that influence independency and how far they influence independency itself. The objectives of this study are examining the individual factors such as etiquete, working experiences, cynicism towards independency and also comparing independency of the students and the auditors, wheter the students of accountancy departments are more independent compared to auditors or vice versa. The samples of this study are the university students of accountancy department which have already taken AUDIT I and public accountant offices in Surabaya. In analysing the data the writer uses multiple regression. The result of this study shows that various system of etiquete variables change, working experiences, and students cynicism illustrate that the influential contribution of various change of independency variables is 61,3% (R-Square) and the various system of etiquete variables 'change and the auditors cynivism illustrate that various change of independency variables is 63,3% (R-Square). Based on The respondents answers, the writer notices that students are more independent rather than auditors on average.